2019
DOI: 10.1177/1545968319883879
|View full text |Cite
|
Sign up to set email alerts
|

Models of Traumatic Brain Injury in Aged Animals: A Clinical Perspective

Abstract: Traumatic brain injury (TBI) is a major cause of morbidity and mortality in the United States, with advanced age being one of the major predictors of poor prognosis. To replicate the mechanisms and multifaceted complexities of human TBI and develop prospective therapeutic treatments, various TBI animal models have been developed. These models have been essential in furthering our understanding of the pathophysiology and biochemical effects on brain mechanisms following TBI. Despite these advances, translating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 122 publications
0
17
0
Order By: Relevance
“…Patients with TBI typically experience sleep disturbances both immediately following TBI and months or years after the initial injury (Baumann, 2012; Baumann et al., 2007; Imbach et al., 2016; Sandsmark et al., 2017). Yet, data regarding how TBI affects sleep in the elderly remain sparse, as most research has overwhelmingly focused on young adults and juveniles (Iboaya et al., 2019). A seminal study of elderly patients recently reported that sleep disturbances were more prevalent in older adults that incurred a TBI than in age‐matched adults without a history of TBI (Wei et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with TBI typically experience sleep disturbances both immediately following TBI and months or years after the initial injury (Baumann, 2012; Baumann et al., 2007; Imbach et al., 2016; Sandsmark et al., 2017). Yet, data regarding how TBI affects sleep in the elderly remain sparse, as most research has overwhelmingly focused on young adults and juveniles (Iboaya et al., 2019). A seminal study of elderly patients recently reported that sleep disturbances were more prevalent in older adults that incurred a TBI than in age‐matched adults without a history of TBI (Wei et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The secondary lesions occur after a period lasting from a few hours to a few days after the primary lesion and they are the result of a tandem of subsequent, metabolic, cellular, and molecular events, which lead in the end to the increase of brain cell death, tissular, vascular and degenerative lesions [ 25 , 26 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Aging, in general, is associated with cellular, molecular, anatomical, and physiological changes ( 74 ). There are likely also intrinsic processes unique to the aged brain that may promote seizure susceptibility ( 75 ).…”
Section: Potential Neurobiological Mechanismsmentioning
confidence: 99%
“…Mitochondrial dysfunction is another pathological feature of both aging and epilepsy ( 78 , 91 ) ( Figure 1 ), which can lead to endogenous production of ROS and apoptosis ( 74 ). Mitochondria fulfill their diverse functions partly through constant remodeling via fission and fusion ( 78 , 91 ).…”
Section: Potential Neurobiological Mechanismsmentioning
confidence: 99%